Integrating Learning Media to English Vocabulary Acquisition in Elementary School - Bulu, Maria Magdalena; Dewi, Ni Putu Artila; Fatmawan, Aditya Ridho (Riwayat: Educational Journal of History and Humanities, 2025)
This study explores the integration of learning media into English vocabulary acquisition among elementary school students. Grounded in Constructivist, Information Processing, and Multi-Modal Learning theories, the research investigates how visual, auditory, and digital tools enhance vocabulary mastery in young learners. A qualitative descriptive method was employed, involving classroom observations and semi-structured interviews with 4th-grade students and teachers at SDK Santo Yosep Tegal Jaya in Bali. The findings reveal that learning media, especially audiovisual tools such as videos and interactive applications, significantly improve students' motivation, engagement, and vocabulary retention. Students reported greater interest and comprehension when vocabulary was introduced through visually rich and contextually meaningful media. Teachers also observed that students demonstrated improved participation and confidence in using new vocabulary. However, several challenges were identified, including limited technological infrastructure, time-consuming lesson preparation, and varying student learning preferences. Despite these obstacles, the integration of media proved effective in creating dynamic, learner-centered classrooms. The study emphasizes the importance of aligning instructional content with appropriate media tools, professional development for teachers, and institutional support for technological access. Overall, the use of learning media fosters active participation, supports differentiated instruction, and bridges the gap between theoretical knowledge and real-world language use. The research advocates for broader implementation of learning media in elementary vocabulary instruction to enhance educational quality and student language outcomes.